'I Myself am an Israelite': Paul, Authenticity and Authority. (December 2017) - Eyl, Jennifer
This article argues that Paul prefers to present himself as an Israelite instead of a Judean for strategic purposes (Phil. 3.5; 2 Cor. 11.13; Rom. 9.4 and 11.1). I examine how Paul simultaneously makes use of claims to ethnic authenticity and his connection to the primordial past in authorizing his gospel message. The article draws on contemporary and ancient comparanda to demonstrate the appeal and function of discourses of ethnicity and antiquity in attracting and convincing Gentile followers. I use anthropological models of 'instrumental authenticity' and 'situational ethnicity' to examine Paul's claims, and suggest that scholars' traditional arguments of insider (Israelite) vs outsider (Judean) language do not go far enough; insider/outsider claims are more complex than scholars have allowed, and using the aforementioned anthropological models sheds light on Paul's construction of his own authority.